A conception of rights to fight economic inequality - Monereo Atienz, Cristina (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
The so-called vertical inequality is one of the central issues of the international debate in recent years, as its unbridled growth has reached intolerable limits in ethical and economic terms that can no longer be ignored by anyone. The Rights Movement believes that it can offer useful tools for dealing with this unjust situation., while others doubt about the relationship between economic inequality and human rights and about the capacity of human rights to fight against this kind of inequality. In the discussion there are opposing, supporting and intermediate positions on this thesis. A careful analysis of this debate and the concepts involved in it is of fundamental relevance in order to assess the root problem behind the economic, social and cultural rights, which has to do with, among other things, a question of concept and foundation of rights. The aim here is to highlight the main arguments and to critically examine the most questionable definitions and considerations in order to then establish a more robust concept of social rights. A reasonable solution is to combine the project of sufficiency with the project of equality by returning to the foundations of the genuine social rule of law, which gave rise to these rights and which configures them as rights of dignity based on real freedom, substantive equality and also solidarity, which is little mentioned in the debate.